Biosynthesis of Selenium Nanoparticles and Evaluation of Its Antibacterial Activity against Pseudomonas aeruginosa. (25th May 2022) - Shakeri, Fatemeh; Zaboli, Fatemeh; Fattahi, Esmail; Babavalian, Hamid
Abstract : Background . A fundamental component of innate immunity is represented by skin that acts as a first aid against infection. The skin's epithelial barriers, respiratory tract, and eyes directly contacting with the external environment have incremented the probability of infection. The opportunistic pathogen Pseudomonas aeruginosa causes various infections in immunocompromised hosts. In addition, one-third of P. aeruginosa clinical isolates are resistant to three or more antibiotics. Lately, lots of researchers concentrate on halophilic microorganisms due to affordable novel biomolecules. One of these biomolecules is metal nanoparticles. MNPs exhibited antimicrobial functionality against a variety of microbes. Amidst MNPs, SeNPs are one of the most extensively studied. In this study, halophilic bacteria from solar saltern were employed for the biosynthesis of SeNPs. Aim . This study aimed to evaluate the antibacterial properties of SeNPs which are synthesized by halophilic microorganisms. Result . The NPs were synthesized by Halomonas eurihalina intracellularly. The produced SeNPs were identified through various assays such as UV-Vis spectroscopy, XRD, DLS, FTIR, and SEM. UV-Vis spectroscopy confirmed the presence of SeNPs. In addition, the average particle size of SeNPs was 260 nm. FTIR confirmed the presence of the capping agent to inhibit the aggregation of SeNPs. Also, synthesized selenium nanoparticles have a natural crystalline nature that is verified by XRD. SEM also revealed the spherical shape. Furthermore, SeNPs represented significant antibacterial activity against P. aeruginosa . Conclusion . According to the obtained result, biosynthesized SeNPs demonstrated remarkable characteristics that make them profitable nonantibiotics and also decrease the morbidity and mortality associated with tissue infections.